Sustainability and Digital Marketing in Uplifting Micro, Small and Medium Enterprises Product Branding: An Investigative Study - Grace Yulianti; Eri Kusnanto; Mia Christy Patricia; Seger Santoso (Proceeding of The International Conference on Economics and Business, 2022)
This study investigates the role of sustainability and digital marketing in enhancing the branding of Micro, Small, and Medium Enterprises (MSMEs). The aim is to explore how these factors contribute to the branding strategies of MSMEs, particularly in the context of emerging markets. Employing a qualitative approach, the study utilizes a purposive sampling technique to select participants from MSMEs operating in diverse sectors. Data collection involves in-depth interviews and content analysis of digital marketing strategies employed by the selected enterprises. Through thematic analysis, the study examines the interplay between sustainability initiatives, digital marketing efforts, and branding outcomes. Findings reveal the significance of incorporating sustainable practices into branding strategies, alongside the pivotal role of digital marketing channels in enhancing brand visibility and engagement. The study contributes to the understanding of effective branding strategies for MSMEs in leveraging sustainability and digital marketing opportunities to foster brand recognition and competitiveness in the market.